An Evaluation of the Healthy Relationships Program for Male Adolescents in Juvenile Detention: A Mixed Method Approach - Rae-lee Warner; Kristie Dellar; Lynne Roberts (SAGE Open)
Currently, there is limited empirically published Australian studies on effective rehabilitative programs in youth justice. This study used a mixed-methods approach to evaluate the Healthy Relationships program which was designed to challenge attitudes relating to intimate partner violence for male adolescents in detention in Western Australia. Paired group analyses compared pre and post measures of attitudes towards intimate partner violence and traditional gender roles and stereotypes for the total sample ( N  = 65). Given the significant overrepresentation of First Nations youth in detention, additional analyses were also run separately for this group ( n  = 51). Participation in the Healthy Relationships program was expected to reduce participant endorsement of attitudes supporting intimate partner violence and endorsement of attitudes supporting traditional gender roles and stereotypes. Results supported our expectations for the total sample and the First Nations youth sample, indicating significant improvements across all outcomes following program participation. Qualitative analysis of participant program feedback further supported the quantitative results and identified the importance of the therapeutic alliance and incentives-based learning approaches. The findings contribute to the “what works” literature and provide insights into factors that improve positive treatment outcomes for youth in detention. Suggestions for program improvements and future research directions are discussed.